Inhibition of sirtuins 1 and 2 impairs cell survival and migration and modulates the expression of P-glycoprotein and MRP3 in hepatocellular carcinoma cell lines. (1st June 2018) - Ceballos, María Paula; Decándido, Giulia; Quiroga, Ariel Darío; Comanzo, Carla Gabriela; Livore, Verónica Inés; Lorenzetti, Florencia; Lambertucci, Flavia; Chazarreta-Cifre, Lorena; Banchio, Claudia; Alvarez, María de Luján; Mottino, Aldo Domingo; Carrillo, María Cristina
Highlights: Cambinol and EX-527 reduced cell survival and migration. SIRTs 1 and 2 inhibitors increased apoptosis. Cambinol and EX-527 modulated P-gp and MRP3 expression. Abstract: Sirtuins (SIRTs) 1 and 2 deacetylases are overexpressed in hepatocellular carcinoma (HCC) and are associated with tumoral progression and multidrug resistance (MDR). In this study we analyzed whether SIRTs 1 and 2 activities blockage was able to affect cellular survival and migration and to modulate p53 and FoxO1 acetylation in HepG2 and Huh7 cells. Moreover, we analyzed ABC transporters P-glycoprotein (P-gp) and multidrug resistance-associated protein 3 (MRP3) expression. We used cambinol and EX-527 as SIRTs inhibitors. Both drugs reduced cellular viability, number of colonies and cellular migration and augmented apoptosis. In 3D cultures, SIRTs inhibitors diminished spheroid growth and viability. 3D culture was less sensitive to drugs than 2D culture. The levels of acetylated p53 and FoxO1 increased after treatments. Drugs induced a decrease in ABC transporters mRNA and protein levels in HepG2 cells; however, only EX-527 was able to reduce MRP3 mRNA and protein levels in Huh7 cells. This is the first work demonstrating the regulation of MRP3 by SIRTs. In conclusion, both drugs decreased HCC cells survival and migration, suggesting SIRTs 1 and 2 activities blockage could be beneficial during HCC therapy. Downregulation of the expression of P-gp and MRP3 supports the potential application of SIRTs 1 and 2 inhibitions in combination with conventional chemotherapy.